PERLINDUNGAN DATA PRIBADI PENGGUNA DOMPET DIGITAL OVO - Nurul Adliyah; Fitriani Jamaluddin; Muhammad Ashabul Kahfi; Susisanti Susisanti (Al-Amwal : Journal of Islamic Economic Law, 2021)
Digital wallets offer convenience in making transactions because they are cashless, but behind the convenience offered by digital wallets there is a content that is quite crucial, which is related to the collection of personal data for digital wallet users. This study uses a normative method with data collection techniques, namely literature. The results show that when registering a digital wallet and the user agrees to the terms and conditions offered by OVO, OVO has the rights to the user's personal data. In addition, there is no law that specifically regulates the protection of personal data.